Active Tectonic Segmentation on the Micro Plate of Northern Sumatra Based on Distribution of Earthquake Epicenter in July 2020 - Nesia Sabrina Marbun; Melda Panjaitan; Triya Fachriyeni; Eridawati (Yayasan Kita Menulis - JoCPES, 2021)
The main goal of this study to increase awareness of earthquake activity due to local faults that have so far received